An Empirical Analysis of Personal Bankruptcy and Delinquency - Gross, David B.; Souleles, Nicholas S. (Review of Financial Studies, 2002)
This article uses a new dataset of credit card accounts to analyze credit card delinquency, personal bankruptcy, and the stability of credit risk models. We estimate duration models for default and assess the relative importance of different variables in predicting default. We investigate how the propensity to default has changed over time, disentangling the two leading explanations for the recent increase in default rates—a deterioration in the risk composition of borrowers versus an increase in borrowers’ willingness to default due to declines in default costs. Even after controlling for risk composition and economic fundamentals, the propensity to default significantly increased between 1995 and 1997. Standard default models missed an important time-varying default factor, consistent with a decline in default costs.